INVESTASI DALAM ASET TAK BERWUJUD DAN NILAI PERUSAHAAN - Andry; Nunung Nuryani (Jurnal Akuntansi, 2022)
In making decisions and predicting the rate of return on investment, earnings are considered the most relevant financial information. However, the 2008 global economic crisis caused the relevance of the value of earnings to decline and could not be relied on in valuing companies, so investors sought other important information that was useful in making decisions, namely information about investment in intangible assets. Therefore, this study aims to examine the effect of investment in intangible assets on firm value. In addition, this study also examines the factors that influence the disclosure of investment in intangible assets in the manufacturing industry. By using purposive judgment sampling technique, samples obtained for model 1 were 69 samples of manufacturing companies, while samples for model 2 obtained an average of 30 sample companies. The data analysis technique used for hypothesis testing is multiple linear regression analysis. The results of this study indicate that the intangible asset investment variable is not proven to have a significant effect on stock prices. Only company size has a significant positive effect on the disclosure of intangible asset investments while Earnings per Share (EPS) and Leverage have no effect. The results of this study can be concluded that investors consider information about intangible asset investment as irrelevant in valuing company equity. In addition, company size has an important role in expressing investment in intangible assets.